Control of iron stress in water-saturated tidal land using ameliorant and its impact on rice productivity - Wahyuni Lestari; Ghulamahdi, Munif; Purwono (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Fe stress is a problem in swamp lands that reduces the growth and yield of rice. Providing various types of ameliorants and selecting rice varieties are considered an effort to obtain high rice productivity in tidal land. The research aimed to study the effect of various ameliorants on rice growth and production, and to obtain high productivity of tolerant variety to iron stress at different locations of tidal land. The research was conducted in Karya Bakti Village (1°10'34.8" S and 104°09’31.1” E), Rantau Rasau, East Tanjung Jabung, Jambi. This study adopted a split-plot design with different types and doses of ameliorant as the main plots and several rice varieties as the subplots with three replications. The results showed that the application of ameliorant rice husk ash, coconut husk ash, empty bunch oil palm compost, and goat manure stimulated vegetative and generative growth. Meanwhile, the Inpari 16 Pasundan variety was proven to have better growth and higher production as described through plant height, fresh weight of shoots and roots, dry weight of shoots and roots, root length, number of productive tillers, number of grains per panicle, 1,000 grain weight, and harvested dry grain. The highest rice production was in the Inpari 16 Pasundan variety, 9.3 tons ha-1 (low-Fe) and 7.6 tons ha-1 (high-Fe). The combination of rice husk ash (0.25 tons ha-1) + coconut husk ash (0.25 tons ha-1) + empty bunch oil palm compost (0.75 tons ha-1) + goat manure (0.75 tons ha-1) was the best combination to increase rice productivity. Inpari 16 Pasundan is considered a tolerant variety on tidal land with high-Fe stress. The interaction between ameliorants and varieties was significant on plant height at ages 2 and 4 weeks after planting at low-Fe, number of productive tillers at high-Fe, root length at low-Fe and high-Fe, 1,000-grain weight, and number of grains per panicle at low-Fe, and harvested dry grain at low-Fe and high-Fe. Keywords: B-type tidal fields, Fe stress cultivation, organic ameliorant, tolerant rice variety, water-saturated cultivation